Development of a Droplet Microfluidics Device Based on Integrated Soft Magnets and Fluidic Capacitor for Passive Extraction and Redispersion of Functionalized Magnetic Particles. Issue 4 (24th February 2020) - Serra, Marco; Gontran, Emilie; Hajji, Ismail; Malaquin, Laurent; Viovy, Jean‐Louis; Descroix, Stephanie; Ferraro, Davide
Abstract: Based on a recent droplet microfluidic device for target molecules' extraction, purification, and redispersion, here an original fluidic control system is proposed to improve the device versatility and usability. This approach relies on the coupling of functionalized magnetic particles handling by integrated soft magnets and a passive droplet splitting control at a channel junction. To reach the high standards required for bioassays' implementation, this device integrates a pressure‐driven variable volume component, acting as a fluidic capacitor, which allows a passive and controlled self‐triggered droplet fingering in a dead‐end channel. The working principle is described, and the modeling of the induced fingering phenomenon by an electric analogy is presented. Then, the achieved finger length is characterized as a function of geometrical and material properties of the fluidic capacitor. The complete device configuration guarantees extraction and purification efficiencies higher than 97% and 95%, respectively, showing high‐throughput particles handling between droplets with a passive droplet splitting control. Finally, this technology is successfully applied to gene expression study for cancer diagnosis by performing magnetic particle–based messenger RNA (mRNA) extraction followed by reverse transcription (RT) and quantitative polymerase chain reaction (RT‐qPCR) analysis. Abstract : A droplet microfluidic device is proposed and validated for target molecules' extraction, purification, and redispersion. This approach relies on the coupling of functionalized magnetic particles handling by integrated soft magnets and a drop‐triggered fluidic capacitor, allowing a passive splitting control at a channel junction and leading to high extraction and purification efficiencies in a wide range of flow rates.